PENGARUH ONLINE CREDIT SERVICES DAN PROMOSI PENJUALAN TERHADAP ONLINE IMPULSE BUYING MAHASISWA PENDIDIKAN EKONOMI - Rieke Septyan Ayusla; Feri Setyowibowo (FKIP Unswagati, 2025)
Online shopping has become an increasing trend among students, particularly supported by digital credit services and various promotional strategies offered by e-commerce platforms. However, these conveniences also encourage impulsive buying behavior, especially among young consumers with varying levels of financial literacy. This study aims to analyze the influence of online credit services and sales promotions on impulse buying behavior among Economics Education students from the 2021–2024 cohorts. The research population consisted of all active students in the program, with 100 respondents selected as the sample, all of whom had used online credit services such as Shopee Paylater, Gopay Later, or Kredivo. Data were collected through an online questionnaire distributed via Google Forms using a 1–4 Likert scale. Moderated regression analysis was applied to examine both direct and interaction effects. The results showed that online credit services and sales promotions had a positive and significant effect on students’ online impulse buying. Furthermore, consumer characteristics acted as a moderating variable with different roles: they weakened the relationship between online credit services and impulse buying, while strengthening the relationship between sales promotions and impulse buying. These findings indicate that consumer emotions and knowledge can either control or enhance impulsive behavior depending on external stimuli. The study highlights the importance of financial literacy as a key factor in helping students manage digital credit facilities and resist aggressive marketing strategies. Keywords: online credit services, sales promotion, online impulse buying, consumer characteristics.